The Concept of Movement according to Ibn Sina - مهلوبي برهان; درواش هبه (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
We try through this research to focus on a basic and important issue, which is movement according to Ibn Sina, as we deal in it with his definition of movement, in which he was not limited to the ideas of force and action, but looked at it from another angle, explaining the most important matters that movement requires and is related to, and we try to show the difference Between movement and change so that we can identify the most important categories in which movement occurs without the other ten categories and their connection to the place, and we try to show Ibn Sina’s position on movement in itself in terms of its unity, its abundance, its measures and its contradiction, and how he responded to all the objections related to movement and its provisions.